Co-located offshore wind–wave energy systems: Can motion suppression and reliable power generation be achieved simultaneously?. (1st February 2023) - Meng, Fantai; Sergiienko, Nataliia; Ding, Boyin; Zhou, Binzhen; Silva, Leandro Souza Pinheiro Da; Cazzolato, Benjamin; Li, Ye
Abstract: Floating offshore wind turbines (FOWTs) present a cost-competitive advantage over their fixed-bottom counterparts, but also have technical challenges of achieving the desired stability and power reliability of the wind turbine. It is believed that co-locating of wave energy converters (WECs) and a FOWT can be the solution to these challenges. However, as the power generation of WECs is strongly associated with their hydrodynamic response, their addition tends to have a detrimental effect on the FOWT's performance. To address this challenge, this paper proposes a framework for combining a FOWT with a small wave array that will make it possible to simultaneously achieve a reliable overall power production, and minimise the motion of a floating platform. It is done by properly controlling the hydrodynamic coupling between FOWT and WEC via a model predictive control approach. The results demonstrate that this novel approach manages to achieve platform stability and power reliability simultaneously, although it might require to collaborate with an aerodynamic control at high wind speeds. This work can be used as a guidance for operation of co-located wind–wave power systems. Highlights: A novel control framework for co-located wind–wave power system is proposed. The platform and power reliability of floating offshore wind turbines are achieved. Up to 46% peak reduction in nacelle velocity and acceleration can be achieved. The power shortage of the FOWT at low wind speeds can be fully compensated.